How do various types of regions attract creative industries? Comparison of metropolitan, old industrial and rural regions in Czechia - Ženka, Jan; Slach, Ondřej (Hungarian Geographical Bulletin, 2018)
In this paper we aim to describe and explain current spatial distribution of creative industries in Czechia. We ask to what extent are localisation patterns of creative industries influenced by specific local contexts. Therefore, we employed a typology of regions (close to local labour areas) that may explain spatial distribution of creative industries: metropolitan cores, metropolitan hinterlands, old industrial regions, urban and rural regions. We use general linear models combining the regional typology as a fixed factor and four covariates – employment density, density of cultural industries, mean firm size in creative industries and diversity of economic activities. We employed horizontal localisation quotient of regional employment in creative industries for the year 2014 as a dependent variable. Our main finding is that the regional typology explains a higher share of variability of the dependent variable (relative specialisation in creative industries) than any other explanatory variable. However, after exclusion of metropolitan cores, the model lost a significant amount of its explanatory power. Urban size/density and position in urban hierarchy are the key explanatory variables. We found only limited empirical evidence that regional contexts affect localisation of CI – regions of similar population/economic size do not differ significantly in spatial concentration of CI.